MANAJEMEN GURU KORDINATOR PENDIDIKAN SKI DALAM MEMBENTUK KARAKTER RELIGIUS DAN DISIPLIN DI PONDOK MODERN - Muhammad Mifta Farid; Imam Fauji (UIN Sumatera Utara Medan, 2025)
This research study aims to analyze the management of the Islamic Cultural History (SKI) coordinator teacher in forming religious character and discipline of students at the eLKISI Modern Islamic Boarding School. The background of this study is the challenge of character education in Indonesia, where many young generations experience a decline in religious and discipline values due to the influence of juvenile delinquency. Using a descriptive qualitative method, this study highlights the implementation of four POAC management functions: planning, organizing, implementing, and supervising. Planning is done by preparing a Learning Implementation Plan (RPP) that integrates religious and discipline values. Organizing involves dividing tasks between teachers and coordinators to ensure effective implementation. Learning methods such as lectures, discussions, and projects based on historical values are applied contextually to instill student character. Supervision through routine evaluations ensures the success of learning. The results of the study indicate that the structured management of the education coordinator teacher is able to improve the formation of religious and disciplined character, despite challenges such as differences in student understanding and time constraints.